Transnational Hispaniola : new directions in Haitian and Dominican studies - Mayes, April J.; Jayaram, Kiran (University of Florida Press, 2018)
This is an edited volume that seeks to elaborate new methodologies and forge new questions in research about Haiti and the Dominican Republic.